IMPLEMENTING THE SMART CITY POLICY IN PALU: GOVERNMENT CHALLANGES AND EFFORTS - Gafar, Iqbal H. Hasan; Nurrahman, Agung (Fakultas Politik Pemerintahan, 2024)
Palu City is one of the cities in Indonesia that implements smart city initiatives. The quality of the Electronic Based Government System (EBGS) index is a crucial aspect of implementing a smart city. According to the 2021 EBGS index results, Palu City was classified as deficient. This study seeks to provide an overview and analyze the implementation of smart city strategies in Palu City. The research methodology employed is qualitative, utilizing data collection approaches such as semi-structured interviews, observation, and documentation. The findings indicate that the smart city concept has yet to be implemented in Palu City. Numerous aspects have yet to be accomplished, including the infrastructure required for implementing the smart city concept. The smart city strategy in Palu City is facilitated by issuing a decree that establishes the smart city implementation team and the smart city development council. These entities involve all regional offices and organizations in Palu City. Overall, implementing smart city policies in Palu City has been poorly coordinated and needs improvement in several areas, including communication, resources, attitudes, and bureaucratic structure.